Peran Penyuluh Pertanian dalam Perubahan Perilaku Petani Padi Desa Tinggar Kecamatan Kadugede Kabupaten Kuningan - As'ari, Muhamad Hilmy Anwar; Sadeli, Agriani Hemita (Universitas Galuh, 2024)
This study is a descriptive qualitative research conducted from March to June 2024 in Tinggar Village, Kadugede District, Kuningan Regency, West Java Province. The choice of research location was based on the following considerations: (1) the location faced issues of declining productivity, (2) farmers' enthusiasm in participating in extension activities was high, but there has been a decline in production over the past three years. The research technique used was a survey. Data were obtained from interviews with questionnaires, observations, and literature reviews. Respondents consisted of one field extension agent and 64 rice farmers participating in agricultural extension activities. They were selected using Purposive Sampling, where the researcher asked the village head to gather members of farmer groups in the village. The results of this study indicate that the role of agricultural extension in Tinggar Village is considered good, leading to changes in the behavior of rice farmers. This is because farmers perceive that the extension activities have a positive impact on production when they follow the advice given by the extension agents. However, changes in behavior are not fully followed by farmers due to cost constraints, resulting in farmers only implementing some of the advice given by the extension agents.